2022
DOI: 10.3390/plants11202703
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of Wall-Associated Kinase (WAK) Gene Family in Cannabis sativa L.

Abstract: Wall-associated kinases (WAKs) are receptors that bind pectin or small pectic fragments in the cell wall and play roles in cell elongation and pathogen response. In the Cannabis sativa (Cs) genome, 53 CsWAK/CsWAKL (WAK-like) protein family members were identified and characterized; their amino acid lengths and molecular weights varied from 582 to 983, and from 65.6 to 108.8 kDa, respectively. They were classified into four main groups by a phylogenetic tree. Out of the 53 identified CsWAK/CsWAKL genes, 23 CsWA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…The present study recorded that the intron-exon structure of CrWAK genes resembles those reported in cotton (Dou et al 2021) and Cannabis (Sipahi et al 2022). The presence of a variety of cis-acting elements in the promotor region of CrWAK genes suggested their involvement in hormone-mediated developmental processes and stress responses.…”
Section: Discussionsupporting
confidence: 76%
“…The present study recorded that the intron-exon structure of CrWAK genes resembles those reported in cotton (Dou et al 2021) and Cannabis (Sipahi et al 2022). The presence of a variety of cis-acting elements in the promotor region of CrWAK genes suggested their involvement in hormone-mediated developmental processes and stress responses.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, a total of 98 SbWAK/SbWAKL proteins were identified in sorghum compared to 100 in maize (Zuo et al, 2015), 125 in rice (de Oliveira et al, 2014), 115 in Brachypodium (Wu et al, 2020), 91 in barley (Tripathi et al, 2021), 68 in rose (Liu et al, 2021), 53 in cannabis (Sipahi et al, 2022), 44 in apple (Zuo et al, 2019), 26 in Arabidopsis (Verica & He, 2002), 29 in tomato (Sun et al, 2020), 58, 68 and 99 in cotton (Gossypium arboreum, G. raimondii, and G. hirsutum, respectively) (Zhang et al, 2021), and 29 in potato (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…The Juglans regia WAK9, the homolog of CsWAK1, has been demonstrated to be involved in pathogen response [46]. A recent analysis of the WAK gene family in Cannabis sativa investigated some CsWAKs/CsWAKLs (CsWAK1, CsWAK4, CsWAK7, CsWAKL1, and CsWAKL7) in leaf tissues, showing how their expression differs from their homologs in other plants [47]. Furthermore, the hemp WAK1 gene is highly expressed under drought stress conditions, and its expression can be induced by phytohormones like salicylic acid, methyl jasmonate, and ethylene [48].…”
Section: Overview Of Cannabis Resistance Genes To Pathogensmentioning
confidence: 99%